Modelling of Malaysia House Price Index - Saudin, Sharmila; Ab Malek, Isnewati; Jehani, Nur Ashakirin; Mastani, Nur Amaelya (2020)
In Malaysia, house price is considered high at a certain part of the country causing the lower and middle groupsunable to purchase a house. The aim of this study is to study the trend of the House Price Index and to identify the suitable model of the Malaysia House Price Index. The data was obtained from the Valuation and Property Services department (JPPH), Department of Statistics Malaysia and Bank Negara. The data was collected over 10 years from 2010 to the first quarter of 2019. Box-Jenkins methodology is applied in determining the best Autoregressive Integrated Moving Average (ARIMA) model of the House Price Index (HPI) in Malaysia. The general finding of this study is that the HPI shows an upward trend for the past nine years but slightly drops in the first quarter of 2019. This study has found out that ARIMA (1,2,1) is the best model for the HPI since it has the smallest value of AIC, BIC and Hannan-Quinn.